Position of Adopted Children in Leaving Appointment Parent's Assets According To Islamic Law, Civil Law & Custom Law - Muhammad Farid; Ahmad Khisni; Munsharif Abdul Chalim (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
In Islam, adoption is known as tabann, Wahbah al-Zuhaily gives the understanding that adoption (tabann) is the taking of a child by someone to a child whose lineage is clear and then the child is assigned to him. One of the supporting factors for the realization of a household in accordance with this Islamic concept is property which is Zinatu al-Hayat, both movable and immovable property, even including securities and intellectual rights Inheritance rights that apply to adopted children to property adoptive parents in Islamic law, civil law, and customary law. Method This approach uses a secondary approach that is normative law or literature writing with a statutory approach. Indonesia adheres to a plural legal system, which means that Indonesia adheres to more than one legal system. This also makes inheritance law divided into three legal systems, namely Western Law, Islamic Law, and Customary Law. In general, the notion of inheritance law is a legal rule that regulates the transfer of property rights, which is the overall rights and obligations of the person who inherits to his heirs and determines who is entitled to receive it. Indonesia adheres to several systems of inheritance law including the civil law system, Islamic law and customary law. In civil law, adopted children still get inheritance rights from their adoptive parents. Then in customary law, the inheritance system used is dependent on the custom where the adopted child lives.